Deep Trade Agreements : Anchoring Global Value Chains in Latin America and the Caribbean - Rocha, Nadia (Washington, DC : World Bank, 2022)
International economic integration offers unexploited opportunities to Latin America and the Caribbean. This report studies how the region’s countries can leverage trade agreements to promote their economies’ participation in global value chains (GVCs).The gaps between potential and actual GVC integration follow from the region’s Economic fundamentals, such as geography, market size, institutions, and factor endowments. But policy choices matter as well. The report, based on new data and evidence, shows that trade agreements can drive policy reforms and help the region overcome some of its disadvantageous fundamentals. The report makes specific policy recommendations to guide Latin American and Caribbean countries in leveraging trade agreements to pursue greater international integration and economic growth. Four main findings emerge from the analysis: (i) Latin America and the Caribbean’s poor international integration and limited participation in GVCs have contributed to its low economic growth over the past decade; (ii) Although the region’s countries increasingly participate in preferential trade agreements (PTAs), there are gaps in the content of these agreements; (iii) Deep trade agreements present an avenue to promote trade and boost GVC integration and upgrading, thus contributing to improved economic performance; (iv) Four areas of deep integration - trade facilitation, regulatory cooperation, services, and state support - are priorities to improve these countries’ GVC participation and upgrading.